Endometrial Cancer: Updates in Molecular Characterization and Treatment Opportunities - Matthew Powell; Marcus Vetter (healthbook TIMES. Oncology Hematology)
Endometrial cancer (EC) is the most prevalent gynecological malignancy and the fifth most common type of female cancer in Switzerland. With an increasing incidence worldwide, EC represents a significant health and economic burden that will continue to grow. This review article aims to provide an overview of topics such as the epidemiology of EC, its risk determinants, advancements in tumor molecular subtyping, how molecular subtyping is changing risk ratification and disease staging, as well as updates to treatment recommendations on patient therapy from international guiding bodies. In particular, the stratification of patients by molecular subtype has led to advances in disease staging and has provided physicians with greater insight into selecting therapies individualized to the patient’s tumor type. We will also review the various treatment modalities available for patients with EC and briefly cover ongoing clinical research in this field, including novel monotherapies and combination therapies in both newly diagnosed and recurrent disease.